Conventional to Early Phase Standardized Uptake Value Ratio on 18F FDG PET/CT Could Reflect Prognosis in Patients with Non-small Cell Lung Cancer - Kupik, Osman; Asa, Sertaç; Eren, Gülnihan (Acta Medica, 2021)
Objective: A high metabolism/perfusion rate in the tumor is known to be factor indicating poor prognosis. The goal of this study was to investigate the prognostic value of the ratio of the conventional standard uptake value to early-phase imaging standard uptake value in patients with newly diagnosed non-small cell lung cancer. Materials and Methods: Early-phase imaging was obtained in the first 120 seconds and conventional imaging was taken after median 66 minutes. The ratio of the conventional standard uptake value to early-phase imaging standard uptake value was calculated. Univariate and multivariate analyses were performed using the Cox proportional hazards regression model to assess the relationship between progression-free survival and ratio of the conventional standard uptake value to early-phase imaging standard uptake. Results: A total of 77 patients with non-small cell lung cancer were recruited. Progression-free survival analysis was performed in 52 inoperable patients. Progression-free survival was found to be related to conventional standard uptake value (p<0.001), tumor size (p<0.001) and ratio of the conventional standard uptake value to early-phase imaging standard uptake in univariate analysis (p=0.047). In the multivariate analysis, ratio of the conventional standard uptake value to early-phase imaging standard uptake (p=0.001, HR=1.145, 95CI%:1.145-1.719) and tumor size (p<0.001, HR=1.026, 95CI%:1.007-1.045) were found to be independent poor prognostic factors. Conclusion: The ratio of the conventional standard uptake value to early-phase imaging standard uptake was found an indicator for prognosis. Evaluating the early phase imaging, without a need for kinetic program or software, without disrupting the routine functioning of the clinic, with conventional imaging may contribute to cancer patient management. There is a need for studies with larger groups of patients.